Մարդպետություն գործակալությունը և մարդպետ պաշտոնյան - Գևորգյան, Հայկազ; Խաչատրյան, Հենրիկ
During the reign of the Armenian Arshakids (66–428), the office of mardpetut‘yun played an important role in the governing system of the country. The official in charge of this agency, the mardpet (in historical sources also mentioned as father, father mardpet, father prince, nerkʿini (internal, eunuch), nerkʿini father, vostikan, loyal), was the direct adviser of the king, the overseer of the royal estates, and the manager of the internal affairs of the royal court. A military regiment called mardpetakan gund and numbering about fifteen thousand people was at his disposal. The mardpets were appointed by the king himself from among the persons most loyal to him. The territories which were given to this office, covered lands from Atrpatakan to Nakhchavan and Chvashrot. In the 5th–7 th centuries, the mardpetakan gund (= Sepukhakan = Vaspurakan) was already mentioned as an independent administrative unit. В период царствования армянских Аршакидов (66-428 гг.) в управлении страной важная роль принадлежала ведомству мардпетутюн (մարդպետություն). Чиновник, возглавляющий это ведомство – мардпет (в исторических источниках упоминается также hайр (Отец), hайр мардпет, hайр ишхан (князь), неркини (дословно – «внутренний», евнух), неркини hайр, востикан, hаватарим (преданный)) являлся непосредственным советником царя, надзирателем царских имений, руководителем внутренних дел царского двора, а также под его началом находилось примерно пятнадцатитысячное войско, именуемое «Мардпетакан гунд». Мардпетов назначал сам царь из числа самых преданных ему лиц. Этому ведомству присваивались территории, именуемые Мардпетакан, которые охватывали земли от Атрпатакана до Нахчавана и Чвашрота. В V-VII вв. Мардпетакан гунд (= Сепухакан = Васпуракан) упоминается уже как самостоятельная административная единица
Keywords: Պատմություն